PENERAPAN PENDEKATAN LEARNING CYCLE (LC) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 9 TENGGAYUN KECAMATAN BUKIT BATU KABUPATEN BENGKALIS - Juliana Juliana; Eddy Noviana; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated by the lack of science learning outcomes of students, with an average grade 57.45. Among students who totaled 33 people only 10 students who completed KKM with classical completeness reached 30.30%. This research is a classroom action research (CAR) conducted aims to improve learning outcomes IPA Elementary School fourth grade students 9 Tenggayun Bukit Batu subdistrict with the application of Learning Cycle Approach (LC). The instrument used for data collection in this study is the Observation Sheet, Questions achievement test and documentation. The results of the research that teachers Activities cycle I and cycle II at the first meeting 62.5%, 70.83% the second meeting, the third meeting 87.5%, and the fourth meeting of 91.66%. Activities of students in the first cycle and the second cycle at the first meeting of 54.16%, 62.5% the second meeting, the third meeting of the fourth meeting of 75% and 83.33%. Learning outcomes of the first cycle and the second cycle, the basic score indicates that finished only 10 people or 30.30% and an incomplete 23 people or 69.70%. At UH I were completed totaling 25 people or 75.76% were not completed 8 people or 24.24%. At UH II that all students completed 31 people or 93.94%. The average value of students also increased, a base score average 57.45% increase student scores on the UH I to 69.24%. While at UH II also increased the average value of student learning outcomes be 75.91%. The results of the study in the fourth grade Negeri 9 Tenggayun Bukit Batu district prove that the application of the approach Learning Cycle (LC can improve learning outcomes IPA fourth grade students of SD Negeri 9 Tenggayun Bukit Batu district. This study concluded that the Implementation Approach Learning Cycle (LC) may increase student learning outcomes, therefore, for schools and classroom teachers to improve student learning outcomes this model can be used as a learning strategy.Key words: Application of Learning Cycle Approach (Lc), Learning Outcomes IPA.